Comparative Proteomic Profiling of Unannotated Microproteins and Alternative Proteins in Human Cell Lines - Cao, Xiongwen; Khitun, Alexandra; Na, Zhenkun; Dumitrescu, Daniel G; Kubica, Marcelina; Olatunji, Elizabeth; Slavoff, Sarah A (Journal of proteome research, 2020)
Ribosome profiling and mass spectrometry have revealed thousands of small and alternative open reading frames (sm/alt-ORFs) that are translated into polypeptides variously termed as microproteins and alt-proteins in mammalian cells. Some micro-/alt-proteins exhibit stress-, cell-type-, and/or tissue-specific expression; understanding this regulated expression will be critical to elucidating their functions. While differential translation has been inferred by ribosome profiling, quantitative mass spectrometry-based proteomics is needed for direct comparison of microprotein and alt-protein expression between samples and conditions. However, while label-free quantitative proteomics has been applied to detect stress-dependent expression of bacterial microproteins, this approach has not yet been demonstrated for analysis of differential expression of unannotated ORFs in the more complex human proteome. Here, we present global micro-/alt-protein quantitation in two human leukemia cell lines, K562 and MOLT4. We identify 12 unannotated proteins that are differentially expressed in these cell lines. The expression of six micro/alt-proteins from cDNA was validated biochemically, and two were found to localize to the nucleus. Thus, we demonstrate that label-free comparative proteomics enables quantitation of micro-/alt-protein expression between human cell lines. We anticipate that this workflow will enable the discovery of regulated sm/alt-ORF products across many biological conditions in human cells.